Epidemiology of honey bee disease and pests in selected zones of Tigray Region, northern Ethiopia - Godifey, G. (Bahir Dar University, 2015)
The study was conducted in Eastern, South-East and Central zones of Tigray region from September, 2014 up to June, 2015 to determine the occurrence and prevalence of honeybee diseases and pests; investigate the effect of honeybee disease and pests inflicted on honey bee colonies and their products; to find out associated potential risk factors for honeybee disease and pests. Questionnaire survey and laboratory diagnostic methods were used for the study. In the questionnaire survey, 384 beekeepers (350 male and 34 female) were interviewed. Similarly, a total of 384 honey bee colonies in 87 apiary sites were examined for the presence of honeybee external parasites and disease pathogens. Regarding honeybee pests and predators, the rank index confirmed that the most important pests and predators affecting honeybee colonies were ants (24.8%), wax moth (24.7%), birds (15.5%), honey badger (13.7%), lizards (9%), spiders (12%) and death head’s hawks moth (5.4%). The total honeybee colonies absconded due to the major honeybee pests was estimated to be 1019(38.8%). About 13%, 12.4%, 9.8% and 3.6% of the colonies absconded were due to wax moth, ants, honey badger and death head’s hawks moth respectively. Colony level prevalence of Varroa mite was 61.2% and 53.4 % during honey flow and dearth period seasons respectively. There was statistically significant (p<0.05) variation in overall prevalence of Varroa infestation between comb age, colony strength, seasons and among agro ecologies (p<0.01).Management affected the observed prevalence of bee lice with the overall colony level prevalence of 27.% and 5.73% during honey flow and dearth period seasons, respectively. Nosema and Chalk brood diseases were detected only during honey flow season with overall colony level prevalence of 38.8% and 16.9%, respectively. Amoeba was observed during the study seasons with highest colony level prevalence of 62.5% during the honey flow season. The result indicated that unlike honeybee pests and predators, the impact of honeybee external parasites and disease pathogens did not significantly affected honeybee colony strength. However, long term seasonal colony monitoring would be recommended.